Rice trade liberalisation and poverty - Gulati, Ashok; Narayanan, Sudha (2003)
This paper explores the important link between rice trade liberalisation and poverty, seeking specifically to respond to two questions: what would be the effect of free trade in rice on trade flow patterns? How will rice trade liberalisation and consequent rice price equalisation across countries influence the prevalence of poverty in the poorer economies? In doing so, the paper focuses primarily on Asia. - Reproduced.
Keywords: Economic liberalization; Poverty; Protectionism; Trade; Free trade